Sustainable Zakat Distribution through Wakalah Contract - Hairunnizam Wahid; Syahmi Haziq Osmera; Mohd Ali Mohd Noor (International Journal of Zakat, 2021)
This study conveys the importance of the skills element in wakalah contract of zakat distribution practiced in Malaysia to ensure the sustainability of continuous zakat distribution. Skillful representatives will manifest good wakalah and simultaneously increase the quality of zakat distribution. This study employed qualitative methodology which was a semi-structured interview method with the Pelaburan Hartanah Berhad (PHB) Company. The skills element becoming the factor for PHB chosen as a research sample is from the entrepreneurial aspect. PHB distributes zakat in a productive form which is in work capital provision. This can facilitate sustainable economic agenda from the aspect of withdrawing asnaf from poverty and ensuring the zakat payment cycle to continue. The informant of interview is a zakat committee member of PHB directly managing the implementation of wakalah in zakat distribution. The results of the study indicated that the wakalah executed by PHB poses several positive impacts such as wider locality of distribution, positive effect from aspect of communal perception on zakat distribution, and positive impact towards the representatives, which is PHB itself. This study imparts several potential suggestions to improve wakalah system of zakat distribution. This study faced several constraints such as research sample and limited types of zakat wakalah. Future studies are suggested to involve more research samples and investigate wakalah from various types of zakat payment.